NUMERICAL ESTIMATE OF CONNECTION DURABILITY OF CONVEYER RUBBER-CABLE BELTS - V. Y. Prushak; O. L. Miranovich (Наука и техника)
The paper considers theoretically and practically important problem that concerns determination of conditions ensuring durability of conveyer rubber cable belt connections. Numerical modeling for destruction process of cable-rubber connections has been developed in the paper. The paper contains analysis of regularities concerning destruction of inter-cable connections and investigates distribution of de-adhesion zones along connections while using a finite element method.